Changes in Distribution and Abundance of the Loggerhead Shrike - Tom J. Cade; Christopher P. Woods (Conservation Biology, 1997)
The Loggerhead Shrike (Lanius ludovicianus) was once widely distributed and common over most of North America, occupying an exclusive breeding range with no other shrikes. Although it occurs in a wide variety of plant associations, this shrike is generally found in landscapes characterized by widely spaced shrubs and low trees interspersed with short grasses, forbs, and bare ground, habitats which include deserts, scrub lands, savannas, and some agricultural settings. The Loggerhead Shrike seems to have been always most abundant in the southern and western portions of its range, with high breeding densities from Florida across the gulf states to Texas and throughout the arid regions of the West. A northeastward expansion in range occurred in the late 1800s in association with deforestation and agriculture. A similar north central expansion occurred in the 1900s with agricultural development of the northern Great Plains and aspen parklands. Contraction and decrease in numbers have been noted in parts of its range since the 1940s, concurrent with the regrowth of forests, loss of pasturelands, and intensive row‐crop agriculture. More recently, Christmas Bird Count data and Breeding Bird Survey data have revealed an overall downward trend across the continent at least since 1966, although numbers are stable or increasing in some locations. Field studies generally implicate alterations in habitat structure and loss of habitat as factors responsible for changes in breeding distribution and overall abundance. Nevertheless, considering its entire distribution in North America and its historical expansions and contractions of range associated with habitat changes, the Loggerhead Shrike does not appear threatened with extinction as a species. We favor a hands‐on approach to management of the critically endangered subspecies, L. l. mearnsi and L. l. migrans, however, and recommend extensive preservation of the natural scrub desert, shrub‐steppe, western oak savanna, and southern savanna vegetation types, which appear to be optimal, core habitats for this species, as well as fostering land‐use practices that favor shrikes in agricultural and suburban landscapes.